Nutritional Content of Bromelain Enzyme Fermented Coconut Dregs as Feed for Oreochromis Niloticus - Kunokwan Netcha; Saengduo Pley; Buonsri Aem (Newinera Publisher, 2021)
The aims of the study is to nutritional content of bromelain enzyme fermented coconut dregs as feed for oreochromis niloticus. The research procedure bromelain enzyme preparation, coconut dregs fermentation process, experimental design. The result of the research is the proximate test that has been carried out on coconut pulp that has been fermented using the bromelain enzyme, it reveals many things. Namely, the water content and ash content of the coconut pulp that has been fermented using the bromelain enzyme is deemed excellent since it displays a value of less than 12 percent . It is different with crude protein which is less than the National Norm on feed since it only displays a value of 6.20 percent when the standard is 20-35 percent . Another with crude fat and crude fiber. Crude fat and crude fiber in coconut dregs that have been fermented with bromelain enzymes have risen and are far from standard. The normal crude fat is only 2-10 percent , whereas the crude fat in coconut pulp after fermentation with bromelain enzymes is more than 20 percent . And the normal crude fiber is only 4-18 percent , this is less than the crude fiber in fermented coconut pulp because it displays more than 29 percent.